Sinergi Q.S. Al-Baqarah Ayat 282 dengan Pencatatan Akuntansi pada UMKM untuk Menjaga Keberlanjutan Bisnis - Fitrotunnisa Hanifah; Selvia Eka Aristantia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to synergize the importance of simple accounting records for MSMEs with Q.S. al-Baqarah verse 282. Where many MSMEs do not implement accounting records even though they are simple. If MSMEs implement this, it can help business sustainability. Allah SWT has commanded business people to record transactions in Q.S. al-Baqarah verse 282. This study uses a qualitative method. The results of the study show that Surah Al-Baqarah verse 282 provides practical and moral guidance that is very relevant to the needs of accounting records in MSMEs. The principles of honesty, accuracy, and justice in this verse are in line with accounting practices that aim to create effective, professional, and sustainable financial management. By implementing these values, MSMEs can face modern business challenges with a strong foundation and oriented towards business sustainability and social harmony. In addition, the application of Qur’anic values can enhance business partners’ trust and improve transparency in transactional relationships. This study recommends that MSMEs strengthen Islamic value-based accounting education to create more trustworthy and competitive financial governance.